The Comparative Performance of MBAs vs. Undergraduate Accounting Majors in Public Accounting. - Wright, Arnold (The Accounting Review, 1988)
ABSTRACT: In response to the greater challenges and competitive pressures facing the public accounting profession in recent years, many CPA firms have hired significant numbers of MBAs. Yet there has been little empirical evidence of the comparative performance in public accounting of MBAs vis-a-vis undergraduates with an accounting major (BAs). This Issue has Important implications as to the appropriate educational training for those entering the profession and for CPA firm recruiting strategies. This study traced the performance of 54 MBA and 56 BA entry level accountants over a nine year horizon. Performance was measured by advancement, turnover, and salary Increases. MBAs advanced more rapidly in the firm than BAs but did not demonstrate significant differences in turnover or salary Increases. MBAs from top rated schools, however, reached the manager level faster and experienced lower turnover rates than other MBAs and BAs.